2012
DOI: 10.7314/apjcp.2012.13.4.1377
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Morphine Inhibits Human Gastric Cancer MGC-803 Cell Growth by Cell Cycle Arrest and Apoptosis Induction

Abstract: Morphine is not only an analgesic treating pain for patients with cancer but also a potential anticancer drug inhibiting tumor growth and proliferation. To gain better insight into the involvement of morphine in the biological characteristics of gastric cancer, we investigated effects on progression of gastric carcinoma cells and the expression of some apoptosis-related genes including caspase-9, caspase-3, survivin and NF-κB using the MGC-803 human gastric cancer cell line. The viability of cells was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
(27 reference statements)
0
22
1
Order By: Relevance
“…In vitro studies have shown the pro-apoptotic action of morphine on cancer cells by different mechanisms including inhibition of NF-κB via nitric oxide [23,24] whereas other studies have shown inhibition of apoptotic processes via p53, a key factor in programmed cell death [25][26][27]. These findings are somewhat conflicting with data showing an inhibitory effect of morphine tumor cell proliferation in vitro [28][29][30][31].…”
Section: Mechanism Favoring Type Of Anesthesia and Cancer Recurrencecontrasting
confidence: 56%
“…In vitro studies have shown the pro-apoptotic action of morphine on cancer cells by different mechanisms including inhibition of NF-κB via nitric oxide [23,24] whereas other studies have shown inhibition of apoptotic processes via p53, a key factor in programmed cell death [25][26][27]. These findings are somewhat conflicting with data showing an inhibitory effect of morphine tumor cell proliferation in vitro [28][29][30][31].…”
Section: Mechanism Favoring Type Of Anesthesia and Cancer Recurrencecontrasting
confidence: 56%
“…The analgesic potency of morphine given intra-articularly is comparable to that of bupivacaine 23 and fentanyl, 24,25 but data regarding the dose-ratio between drugs is heterogeneous. Morphine was reported to induce apoptosis and necrosis in cancer cell lines, 26 but it did not induce any cytotoxic effects in human ham-string progenitor cells. 8 Fentanyl was less cytotoxic than ropivacaine in mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 93%
“…7) We also demonstrated that morphine could suppress the growth and the cell cycle progression of MGC-803 cells, the mechanism of which might be related to activation of caspase-3 and caspase-9, and inhibition of NF-κB nuclear translocation. 8) Some studies have found that at a clinical concentration morphine (0.01 µM) can induce cell apoptosis or necrosis in MCF-7 human tumor cell lines in vitro and inhibit the growth of tumor cells. 9) In addition, morphine (0.1 to 100 µM) and DAMGO (an μ-opioid receptor selective agonist) can inhibit the adhesive and migration of the HEK FLAG-MOP cells, the mechanisms of which are associated with mediation of an opioid receptor.…”
mentioning
confidence: 99%